Human Capital andCEOCompensation during Institutional Transitions - Peng, Mike W.; Sun, Sunny Li; Markóczy, Lívia (Journal of Management Studies, 2015)
AbstractFirms appointCEOswith different types of human capital in order to manage resource dependencies. HowCEOsare compensated thus can be conceptualized as a valuation process of how boards view the value ofCEOs' human capital. Two types of human capital – international experience and political ties – have emerged as potential drivers ofCEOcompensation during institutional transitions. But how they impactCEOcompensation has remained unclear. We develop a resource dependence‐based, contingency framework to focus on theexternalandinternalfactors that enable or constrain human capital to impactCEOcompensation. Because of the tremendous regional diversity withinChina, externally, we focus on the level of marketization of the region in which firms are headquartered. Internally, we pay attention to two corporate governance mechanisms: politically connected outside directors and compensation committee. Data from 10,329 firm‐year observations at 94 per cent of listed firms inChina largely support our framework. Overall, our study contributes to resource dependence research by extending this research to the context of institutional transitions with a focus on how human capital impactsCEOcompensation.